The influence of internal company factors on capital structure: An empirical study of the IDX80 Index for the 2019-2023 period - Safitri, Nur Khofifah; Octavia, Evi (Educoretax, 2025)
Capital structure a crucial role because it directly impacts a company's financial position. Capital structure is a fundamental factor related to a company's funding decisions, both through long-term and short-term debt. This study aims to analyze the effect of sales growth, profitability as measured by Return on Assets (ROA), and asset structure as measured by Tangibility Assets (TA), on capital structure as measured by Debt to Equity Ratio (DER). This study employed a quantitative approach with a purposive sampling technique. The population of the study was 32 companies listed on the IDX80 Index during the 2019–2023 period, resulting in a total of 160 samples. The analysis used panel data regression with Eviews 13 software. The results showed that sales growth, profitability, and asset structure did not affect capital structure in companies listed on the IDX80 index during that period.